Association between erectile dysfunction and the severity of obstruction to airflow in patients with chronic obstructive pulmonary disease - María J. Pareja-Zabala; Carlos Aguirre; Abraham Alí-Munive; María C. Pareja-Zabala; Luis F. Guerrero; Sandra Huertas; Leidy P. Prada; Luis F. Giraldo-Cadavid (Urología Colombiana)
Objectives: The objective of this study was to explore a possible association between ED and the severity of airflow obstruction in patients with COPD. Materials and methods: A cross-sectional study was conducted using the International Index Erectile Function (IIEF), a scale validated and translated to Spanish. Bivariate analyses between subgroups were made for quantitative variables using a t-test for means and Mann–Whitney U for medians; qualitative variables were compared using the χ2 test or Fisher’s test, depending on distribution. Confusion bias in the association between ED and airflow obstruction was controlled using a logistic regression model. Results: The Spanish version of the IIEF-15 scale was valid and applicable to the Colombian population. The prevalence of ED in COPD patients living at high altitudes was similar to that found at sea level. Such prevalence is higher than in general population. Beta-blockers increased 7 times the risk of ED, but we found no association between the degree of airflow obstruction and ED. Conclusion: Although the severity of COPD is not associated with ED, the prevalence of ED in COPD is higher than in general population. Therefore, ED screening in COPD patients using the IIEF could be justified. The strong association between beta-blockers and ED had not been previously described in patients with COPD but must be considered in their clinical management.